The hidden value of artisanal fisheries in Honduras - Steven Canty; Manuela Funes; Stephen Box; Kyrstn Zylich; Brittany Derrick; Esther Divovich; Alasdair Lindop; Daniel Pauly; Dirk Zeller (Fisheries Management and Ecology, 2019)
Declining fisheries catches are a global trend, with management failing to keep pace with growth in fishing effort and technological advances. The economic value of Honduras’ catches was estimated within the industrial and artisanal sectors. Catches were found to be 2.9 times greater than the official statistics between 1950 and 2015. The merging of industrial and artisanal catch data masked the decline in industrial catches and hid the strong growth of artisanal fisheries. In 1996, annual artisanal fisheries landed catches surpassed the industrial fishery sector, and in 2000, the annual net value of artisanal fisheries eclipsed the value of the industrial fisheries. These data highlight the importance of artisanal fisheries in Honduras and challenge the long‐held belief that the industrial sector contributes more to the national economy. The global paucity of fisheries data highlights the need for comprehensive strategies to collect more detailed and accurate fisheries data.